Kadar Gula Darah Lebih Tinggi pada Pasien Hipertensi dengan Delesi Intron 16 Gen Ace - Lowry Yunita; Mohammad Saifur Rohman; Bagus H Kuncahyo; Mifetika Lukitasari; Arina Madjidi; Maulidiyatun Nuril Faizah; Nashi Widodo (The Indonesian Heart Association, 2016)
Background Renin Angiotensin Aldosteron System plays major role in hypertension pathophysiology. Has been proposed that half of individuals with essential hypertension are considered insulin resistant. Angiotensin Converting Enzyme gene polymorphism taking the control of ACE level in human plasma. There might be a correlation between ACE gene polymorphism and plasma glucose level.Objective This study sought to investigate ACE gene polymorphism insertion/deletion in hypertensive patients and its correlation with plasma glucose level.Method A total of 100 hypertensive patients at Saiful Anwar cardiovascular outpatients clinic who received ACEi at least 8 weeks were included. ACE genotype were determined by polymerase chain reaction method, and plasma glucose level was measured by enzymatic colorimetric assay method.Result The II, ID, and DD genotype were observed in 48%, 29% and 23% of participant, respectively. The fasting and 2 hours post prandial plasma glucose were significantly higher in DD genotype patients. The insertion/deletion polymorphisms were not related significantly to age, sex, cough, and controlled blood pressure of those patients.Conclusion This study showed that 23% of hypertensive patients had DD genotype with higher plasma glucose level as compare to those of II and ID genotype.